2005
DOI: 10.1007/s10816-005-2395-7
|View full text |Cite
|
Sign up to set email alerts
|

Zooarchaeology and Historical Archaeology: Progress and Prospects

Abstract: This review assesses the development and current status of zooarchaeological research in historical archaeology. Analytical issues in recovery, identification, quantification and interpretation are discussed with particular reference to assemblages from historical sites. The results section summarizes the substantive contributions zooarchaeological studies of historical assemblages have made to our understanding of past diet, food production systems, social and cultural variation, and archaeological interpreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 79 publications
(111 reference statements)
0
20
0
9
Order By: Relevance
“…Selain itu, para ahli arkeologi pun berusaha membuat sebuah konsep analisis terhadap segala macam pengaruh fauna dalam kehidupan dan interaksi manusia. Model analisis inilah yang kemudian sering disebut sebagai kajian analisis arkeofauna (Davis, 1987;Landon, 2005). Kajian arkeofauna ini memiliki banyak penamaan dan peristilahan (Casteel & Grayson, 1977;Lyman, 1994), meskipun demikian, kajian ini tetap perlu dilakukan dengan pertimbangan pentingnya data kehadiran fauna dalam satu ruang aktivitas jelajah manusia masa lampau.…”
Section: Pendahuluanunclassified
“…Selain itu, para ahli arkeologi pun berusaha membuat sebuah konsep analisis terhadap segala macam pengaruh fauna dalam kehidupan dan interaksi manusia. Model analisis inilah yang kemudian sering disebut sebagai kajian analisis arkeofauna (Davis, 1987;Landon, 2005). Kajian arkeofauna ini memiliki banyak penamaan dan peristilahan (Casteel & Grayson, 1977;Lyman, 1994), meskipun demikian, kajian ini tetap perlu dilakukan dengan pertimbangan pentingnya data kehadiran fauna dalam satu ruang aktivitas jelajah manusia masa lampau.…”
Section: Pendahuluanunclassified
“…A avaliação das condições de formação de um depósito arqueológico preservado com estratigrafia, assim como dos processos e agentes naturais ou antrópicos que levaram à acumulação de restos de natureza animal ou vegetal, em conjunto com os artefactos propriamente ditos, consiste numa das etapas fundamentais do estudo e interpretação de arqueossítios (e.g. CLAASSEN 1998;LANDON 2005). As análises tafonómicas, embora desenvolvidas inicialmente no âmbito da Paleontologia (tafonomia e fossilização), alargaram-se nas últimas décadas aos contextos arqueológicos, facto que faz sentido, dada a componente interdisciplinar de bioarqueologia que estes pressupõem (e.g.…”
Section: Importância Dos Estudos De Tafonomiaunclassified
“…Archaeological studies have shown that colonists also innovatively incorporated native resources into their diets (e.g., Dudek, Kaplan, & King, ; Landon, , ; Reitz & Honerkamp, ; Reitz & Scarry, ). By the 1800s, European colonists had settled into a mixed diet of domesticates raised on local land plots or purchased at markets and wild foods taken opportunistically.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of domestic bird taxa, sister taxa of these species already existed in the New World (e.g., grouse, quail, ducks, turkey, and Canada goose) and as a result could provide similar commodities to domestic taxa. Examination of faunal reports suggests that introduced domesticates—mainly chicken and some goose—and native turkey are most commonly identified, whereas other wild birds consistently, but minimally, augmented diet throughout the Colonial period (Landon, ; Roy, ).…”
Section: Introductionmentioning
confidence: 99%